2018
DOI: 10.5897/ajar2018.13140
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of radish fertilized with different doses of bovine manure

Abstract: The application of organic matter to the soil has considerable benefits for agricultural land, including an improvement in the physical structure and fertility of the soil, which can often be extended from one crop to another. Animal manure is one of the most widely-used types of organic fertilizer, due in part to its availability. The present study investigated the productivity of radish exposed to different doses of bovine manure. The research was conducted at the experimental area of the Nova Xavantina camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is observed that with and without the application of A. brasilense there were increments of 16.5% and 6.40% in RD, respectively (Figure 1A). In agreement with MAIA et al (2018) investigated the productivity of radish fertilized with different doses of bovine manure and obtained a tuber diameter of 3.06 cm. Similar results were observed by RODRIGUES et al (2013), using organic inputs to replace mineral fertilization in radish culture, they verified a 5% increment in root diameter.…”
Section: Discussionmentioning
confidence: 60%
“…It is observed that with and without the application of A. brasilense there were increments of 16.5% and 6.40% in RD, respectively (Figure 1A). In agreement with MAIA et al (2018) investigated the productivity of radish fertilized with different doses of bovine manure and obtained a tuber diameter of 3.06 cm. Similar results were observed by RODRIGUES et al (2013), using organic inputs to replace mineral fertilization in radish culture, they verified a 5% increment in root diameter.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, the use of perlite as a growing medium produced cracked roots due to inadequate water availability [31]. Along with the growing medium, the use of organic fertilizer (70 t ha −1 ) also developed split/cracked roots due to high nitrogen concentration [49]. In radish root development, 4 weeks after sowing is very critical, as during this period the root is expanding rapidly and any kind of irrigation or fertilizer stress during this period is important in producing cracked roots [24].…”
Section: Splitting/crackingmentioning
confidence: 99%